2009
DOI: 10.1097/jnr.0b013e3181a6a601
|View full text |Cite
|
Sign up to set email alerts
|

Successful Mechanical Ventilation Weaning Experiences at Respiratory Care Centers

Abstract: A phenomenological qualitative study was conducted on the experiences of patients who had been successfully weaned from mechanical ventilation, including essential elements of the patient support system during the weaning process. In-depth interviews were conducted with 20 participants who had been recruited through purposive sampling from three respiratory care centers in Taiwan. The experiences of participants who had been successfully weaned from mechanical ventilation could be categorized into five themes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
(39 reference statements)
0
19
0
Order By: Relevance
“…Moreover, fewer patients who received All‐RN care failed to be weaned from the ventilator compared to the patients who received RN/Aide care. As noted in previous qualitative studies, the concern of nurses and close family members for patients is an important factor in the process of being weaned from the ventilator (Chen et al 2009). Our findings support the notion that conscious patients need more psychological support, and that an increase in professional nursing staff to guide the weaning process could effectively reduce patients’ fear and stress.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, fewer patients who received All‐RN care failed to be weaned from the ventilator compared to the patients who received RN/Aide care. As noted in previous qualitative studies, the concern of nurses and close family members for patients is an important factor in the process of being weaned from the ventilator (Chen et al 2009). Our findings support the notion that conscious patients need more psychological support, and that an increase in professional nursing staff to guide the weaning process could effectively reduce patients’ fear and stress.…”
Section: Discussionmentioning
confidence: 96%
“…This finding is congruent that of Yang et al (2012), whose comparison of the effects of two different nursing skill mix models revealed that the patients in the group with 60-70% RNs had lower ventilator weaning rates than the patients in the 100% RN group. Therefore, care from RNs and family is an important factor for successful ventilator weaning (Chen et al 2009). Therefore, care from RNs and family is an important factor for successful ventilator weaning (Chen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have observed that patients experienced impaired communication, deficit of interaction, restlessness, loneliness and loss of control during mechanical ventilator weaning (Schou & Egerod 2008). Therefore, care from RNs and family is an important factor for successful ventilator weaning (Chen et al 2009). During mechanical ventilator weaning, RNs should regularly perform correct and professional evaluations and regularly observe whether patients are experiencing inadequate respiratory muscle endurance, as evidenced by dyspnoea, hyperventilation and inadequate blood oxygen supply.…”
Section: Discussionmentioning
confidence: 99%
“…Most reviews of weaning from mechanical ventilation have examined only quantitative data [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] Range of health care professionals [25][26][27][28][29][30][31][32][33][34][35] Patients only [36][37][38][39][40][41][42][43][44][45] Physicians only (intensivists or anesthetists working in intensive care units) [46][47][48][49] Patients' family members 50,51 Patients and nurses Participant interviews and observation 12,13,27,28,[31][32][33]40<...>…”
Section: Discussionmentioning
confidence: 99%